2015
DOI: 10.1002/cam4.429
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening with clinic‐based Pap test versus home HPV test among Somali immigrant women in Minnesota: a pilot randomized controlled trial

Abstract: Cervical cancer is more common in the Somali immigrant population than the general population in the United States (US). There are low rates of cervical cancer screening among Somali women. This study compares cervical cancer screening test completion rates for a home human papilloma virus (HPV) test and standard clinic Pap test. Sixty-three Somali immigrant women aged 30–70 years who had not undergone cervical cancer screening within the past 3 years were randomly assigned to a home HPV test group (interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 60 publications
(66 reference statements)
1
60
1
Order By: Relevance
“…[25] That our study found a lower cervical screening uptake among Somali women compared to other ethnic groups align with the findings of a randomized control trial pilot study conducted in Minnesota using the same methodological approach of targeting participants outside of a health system or medical home. In this study, only 19.4% Somali women accepted the cervical cancer screening [26] compared to 27% of Somali women in our study. Similar findings were observed in the Boston area where Somali women were found to be less likely to be screened for cervical cancer than Central African women (21.3% vs. 44.1%).…”
Section: Plos Onecontrasting
confidence: 60%
“…[25] That our study found a lower cervical screening uptake among Somali women compared to other ethnic groups align with the findings of a randomized control trial pilot study conducted in Minnesota using the same methodological approach of targeting participants outside of a health system or medical home. In this study, only 19.4% Somali women accepted the cervical cancer screening [26] compared to 27% of Somali women in our study. Similar findings were observed in the Boston area where Somali women were found to be less likely to be screened for cervical cancer than Central African women (21.3% vs. 44.1%).…”
Section: Plos Onecontrasting
confidence: 60%
“…Most studies conducted in the U.S. have found that women were receptive to having an HPV self-test mailed to their home and to completing the test; these studies reported many of the same concerns, especially about correctly completing the test (Galbraith et al 2014; Nelson et al 2015). These findings were similar among immigrant women (Barbee et al 2010; Sewali et al 2015), among lesbian and bisexual women (Reiter and McRee 2015), and underserved women (Crosby et al 2015; Galbraith et al 2014; Montealegre et al 2015). …”
Section: Discussionmentioning
confidence: 52%
“…Recent evidence suggests that vaginal self‐obtained samples provide sensitivity and specificity equal to clinician‐collected specimens for detecting high‐risk HPV types and cervical intraepithelial neoplasia 2+ . HPV self‐testing acceptability, feasibility and satisfaction studies among Indigenous and ethnic minority women found that HPV self‐testing is preferable to cervical cytology, and potentially eliminates barriers to cervical screening …”
Section: Introductionmentioning
confidence: 99%